Anti-HCoV: A web resource to collect natural compounds against human coronaviruses. (December 2020) - Monticolo, Francesco; Palomba, Emanuela; De Santis, Rosa; Assentato, Lorenzo; Triscino, Viviana; Langella, Maria Chiara; Lanzotti, Virginia; Chiusano, Maria Luisa
Abstract: Background: A novel coronavirus, the SARS-CoV2, was revealed to be the cause of COVID19, the pandemic disease that already provoked more than 555.324 deaths in the world (July 10, 2020). No vaccine treatment has been defined against SARS-CoV2 or other human coronaviruses (HCoVs), including those causing epidemic infections, neither appropriate strategies for prevention and care are yet officially suggested. Scope and approach: We reviewed scientific literature on natural compounds that were defined as potentially effective against human coronaviruses. Our desk research identified non-chemically modified natural compounds that were shown (in vitro) and/or predicted (in silico) to act against one or more phases of human coronaviruses cell cycle. We selected all available information, merged and annotated the data to define a comprehensive list of natural compounds, describing their chemical classification, the source, the action, the specific target in the viral infection. Our aim was to collect possible compounds for prevention and care against human coronaviruses. Key findings and conclusions: The definition of appropriate interventions against viral diseases need a comprehensive view on the infection dynamics and on necessary treatments. Viral targeting compounds to be exploited in food sciences could be of relevant interest to this aim. We collected 174 natural compounds showing effects against human infecting coronaviruses, providing a curated annotation on actions and targets. The data are available in anti-HCoV, a web accessible resource to be exploited for testing and in vivo trials. The website is here launched to favour a community based cooperative effort to call for contribution and expand the collection. To be ready to fight. Highlights: The new SARS-CoV2 caused more than 555.000 deaths in seven months. HCoVs similarities suggest possible similar action against them. No official treatment for prevention and care against HCoVs is yet approved. In silico and experimental analyses revealed effective compounds against HCoVs. Comprehensive collections of natural compounds against HCoVs are a resource.